SARS-CoV-2 effects on tourism. The recovery of regional complexity: When less means more: The case of Balearic Islands - Hugo Capellà Miternique (Research in Globalization, 2021)
The global effects of the pandemic have had a strong impact on tourism. However, the process of transformation began earlier, with the emergence of new technologies and social and cultural changes. Covid-19 has accelerated the diversification process and increased the degree of interrelation with other sectors, creating a more plural and complex perspective. The importance of tourism in the Balearic Islands makes this region an excellent case study for analyzing the current processes of change and their disparate consequences. Against this background, tourism in the archipelago is directed to follow the tenet of 'less is more', in a clear commitment to incentivizing exclusivity as a driver of the complex regional renewal of the Balearic Islands. In this article, after debating the paradigm shift in tourism from a qualitative perspective, we will analyze examples of changes in access to the islands and its effects on sun-and-beach tourism. Additionally, we will analyze cases that allow us to begin to define the pillars of a new, more complex view of tourism that encompasses diversification (spatial, practical and economic) and exclusivity realigned with the regional scale (Balearic). We will conclude by describing the change in the economic paradigm that points towards the enhancement of regional complexity as a guarantee of strength within the global context.
Keywords: 330; Tourism; Covid-19; Regional; Diversification; Complexity; Exclusivity